A mobile application for ECG detection and feature extraction - Stojmenski, Aleksandar; Gushev, Marjan; CHorbev, Ivan (My University, 2016)
This paper presents a system for early detection and alerting of the onset of a heart attack. The system consists of a wireless, easy wearable and mobile ECG biosensor, a cloud based data center, smartphone and web application. A significant part in the system is the 24h health monitoring and care provided by expert cardiac physicians. The system predicts potential heart attack and sends risk alerts to the medical experts for assessment. If a potential heart attack risk exists, ambulance is being called with the coordinates of the cardiac patient wearing the sensor. The timely reaction can prevent serious tissue damage or even death to the users of the system.
Keywords: electrocardiogram, sensors, cloud, Internet of things, medical application, heart monitoring